Clinical profile of acute kidney injury in neonatal sepsis and perinatal asphyxia using nRIFLE and modified KDIGO criteria - Subramanian, Sharan; Malik, Sushma; Wade, Poonam Abhay (Indian Journal of Child Health, 2019)
Background: Newborn babies with sepsis and perinatal asphyxia form a high-risk group for developing neonatal acute kidney injury (nAKI). The diagnosis and staging of nAKI is challenging and has several limitations. Objective: The objectives of this study were to estimate the hospital-based incidence of nAKI in septic and asphyxiated neonates, describe their clinical profile and outcome, and compare the two classifications – neonatal risk, injury, failure, loss, and end-stage renal disease (nRIFLE) and neonatal modified Kidney Disease: Improving Global Outcomes (KDIGO) criteria for their agreement. Materials and Methods: Consecutive neonates who fulfilled the diagnosis of sepsis or perinatal asphyxia were included in this prospective cohort study. Urine output was monitored 6 hourly by diaper weight and serum creatinine every 48 h or earlier if required. The clinical profile and outcome of neonates who developed AKI were studied, and AKI was staged using both nRIFLE and KDIGO criteria. Chi-square test was used to test the association of risk factors with AKI, Pearson’s Chi-square and Kappa statistics were used to compare the two staging criteria. Results: Of 90 neonates enrolled, the incidence of AKI in sepsis was 145/1000 neonates and perinatal asphyxia was 464/1000 neonates. AKI was maximally observed in the early preterm neonates (45.4%) and very low birth weight neonates (36.36%). Oliguria was present in a majority of the neonates with nAKI but varied according to the classification system used. nAKI was significantly associated with high mortality (54.2%) (p